Global imprint of historical connectivity on freshwater fish biodiversity. (9th July 2014) - Dias, Murilo S.; Oberdorff, Thierry; Hugueny, Bernard; Leprieur, Fabien; Jézéquel, Céline; Cornu, Jean‐François; Brosse, Sébastien; Grenouillet, Gael; Tedesco, Pablo A.; Anderson, Marti
Abstract The relative importance of contemporary and historical processes is central for understanding biodiversity patterns. While several studies show that past conditions can partly explain the current biodiversity patterns, the role of history remains elusive. We reconstructed palaeo‐drainage basins under lower sea level conditions (Last Glacial Maximum) to test whether the historical connectivity between basins left an imprint on the global patterns of freshwater fish biodiversity. After controlling for contemporary and past environmental conditions, we found that palaeo‐connected basins displayed greater species richness but lower levels of endemism and beta diversity than did palaeo‐disconnected basins. Palaeo‐connected basins exhibited shallower distance decay of compositional similarity, suggesting that palaeo‐river connections favoured the exchange of fish species. Finally, we found that a longer period of palaeo‐connection resulted in lower levels of beta diversity. These findings reveal the first unambiguous results of the role played by history in explaining the global contemporary patterns of biodiversity.